Cognitive Profiles of Developmental Dysgraphia - Döhla, Diana; Willmes, Klaus; Heim, Stefan (Frontiers in Psychology, 2018)
Developmental dysgraphia is a disorder of writing/spelling skills, closely related to developmental dyslexia. For developmental dyslexia, profiles with a focus on phonological, attentional, visual or auditory deficits have recently been established. Unlike for developmental dyslexia, however, there are only few studies about dysgraphia, in particular about the variability of its causes. Research has demonstrated high similarity between developmental dyslexia and dysgraphia. Thus, the aim of the study was to investigate cognitive deficits as potential predictors of dysgraphia, analogously to those for dyslexia, in order to identify dysgraphia profiles, depending on the particular underlying disorder. Different tests were carried out with 3rd and 4th grade school children to assess their spelling abilities, tapping into phonological processing, auditory sound discrimination, visual attention and visual magnocellular functions as well as reading. A group of 45 children with developmental dysgraphia was compared to a control group. The results showed that besides phonological processing abilities, auditory skills and visual magnocellular functions affected spelling ability, too. Consequently, by means of a two-step cluster analysis, the group of dysgraphic children could be split into two distinct clusters, one with auditory deficits and the other with deficits in visual magnocellular functions. Visual attention was also related to spelling disabilities, but had no characteristic distinguishing effect for the two clusters. Together, these findings demonstrate that a more fine-grained diagnostic view on developmental dysgraphia, which takes the underlying cognitive profiles into account, might be advantageous for optimizing the outcome of individuum-centered intervention programs.